1992
DOI: 10.1016/0735-1097(92)90043-m
|View full text |Cite
|
Sign up to set email alerts
|

Does thrombolysis in myocardial infarction (TIMI) perfusion grade 2 represent a mostly patent artery or a mostly occluded artery? Enzymatic and electrocardiographic evidence from the TEAM-2 study

Abstract: One measure of the success of thrombolysis is the early patency status of the infarct-related coronary artery. The Thrombolysis in Myocardial Infarction (TIMI) study group designated patency grades 0 (occluded) or 1 (minimal perfusion) as thrombolysis failure and grade 2 (partial perfusion) or 3 (complete perfusion) as success. To evaluate their true functional significance, perfusion grades were compared with enzymatic and electrocardiographic (ECG) indexes of myocardial infarction in 359 patients treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(38 citation statements)
references
References 27 publications
2
34
0
2
Order By: Relevance
“…Improved epicardial blood flow assessed by use of either TIMI flow grades [1][2][3][4][5][6] or the TIMI frame count 7,8 has been related to reduced mortality after thrombolytic administration. The data presented here indicate that improved myocardial perfusion at 90 minutes after thrombolytic administration is related to reduced mortality independent of epicardial blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved epicardial blood flow assessed by use of either TIMI flow grades [1][2][3][4][5][6] or the TIMI frame count 7,8 has been related to reduced mortality after thrombolytic administration. The data presented here indicate that improved myocardial perfusion at 90 minutes after thrombolytic administration is related to reduced mortality independent of epicardial blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…W hereas improved epicardial blood flow (as assessed with either TIMI flow grades [1][2][3][4][5][6] or the TIMI frame count 7,8 ) has been related to reduced mortality after administration of thrombolytic drugs, the relationship between tissue-level microvascular perfusion and mortality has not been examined in a large number of patients after thrombolytic administration. This study describes the development and use of a simple semiquantitative classification scheme, the TIMI myocardial perfusion grade (TMP), that can be used to characterize the filling and clearance of myocardial perfusion from a coronary angiogram.…”
mentioning
confidence: 99%
“…Only post-procedural Thrombolysis in Myocardial Infarction (TIMI) flow grade 3 improves outcomes in patients with STEMI. Although it was shown that prognosis in patients with final TIMI flow grade 2 does not differ from that in patients with TIMI flow grade 0-1, this conclusion was based on the results of outdated studies involving acute myocardial infarction (AMI) patients treated with thrombolytic therapy [5][6][7]. Thus, there is a paucity of data on the association between angiographic findings and clinical outcomes in patients with myocardial infarction (MI) without ST-segment elevation undergoing percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…It has been a valuable tool to compare angiographic outcomes following reperfusion, and the association of the TFGs with clinical outcomes (including mortality) has been well documented. [2][3][4][5][6][7][8] The relationship between TFG and mortality does satisfy what some consider to be 3 criteria required to validate a surrogate end point for mortality, as follows: (1) There is an association between TIMI grade 3 flow and mortality, (2) an agent such as recombinant tissue plasminogen activator improves TIMI grade 3 flow by 22% over another agent such as streptokinase, and (3) the agent tissue plasminogen activator improves mortality 1.1% over streptokinase.…”
Section: Timi Flow Grades (Tfgs)mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] It has become increasingly apparent, however, that clinical outcomes are not only associated with angiographic flow in the epicardial artery, but also with angiographic flow in the myocardium. 9 -13 To this end, the goal of reperfusion therapies has shifted to include reperfusion downstream at the level of capillary bed, and it might be more appropriate that the hypothesis now be termed "the time dependent open artery and open microvascular hypothesis."…”
mentioning
confidence: 99%